Leukocyte telomere length is associated with MRI‐thigh fat‐free muscle volume: data from 16 356 UK Biobank adults - Ben Kirk; Chia‐Ling Kuo; Peiran Liu; Meiruo Xiang; Jacob E. Earp; Jatupol Kositsawat; George A. Kuchel; Gustavo Duque (Wiley, 2024)
Abstract Background Telomere attrition may share common biological mechanisms with bone and muscle loss with aging. Here, we investigated the association between these hallmarks of aging using data from UK Biobank, a large observational study. Methods Leukocyte telomere length (LTL as T/S ratio) was measured using a multiplex qPCR assay at baseline (2006-2010). Bone mineral density (whole body and regional; via dual‐energy X‐ray absorptiometry), trabecular bone score (via lumbar‐spine dual‐energy X‐ray absorptiometry images), fat‐free muscle volume (thighs; via magnetic resonance imaging), and muscle fat infiltration (thighs; via magnetic resonance imaging) were measured during the imaging visit (2014-2018). Regression models were used to model LTL against a muscle or bone outcome, unadjusted and adjusted for covariates. Results A total of 16 356 adults (mean age: 62.8 ± 7.5 years, 50.5% women) were included. In the fully adjusted model, thigh fat‐free muscle volume was associated with LTL in the overall sample (adjusted standardized β (aβ) = 0.017, 95% CI 0.009 to 0.026, P < 0.001, per SD increase in LTL), with stronger associations in men (aβ = 0.022, 95% CI 0.010 to 0.034, P < 0.001) than in women (aβ = 0.013, 95% CI 0.000 to 0.025, P = 0.041) (sex‐LTL P = 0.028). The adjusted odds ratio (aOR) for low thigh fat‐free muscle volume (body mass index‐adjusted, sex‐specific bottom 20%) was 0.93 per SD increase in LTL (95% CI 0.89 to 0.96, P < 0.001) in the overall sample, with stronger associations in men (aOR = 0.92, 95% CI 0.87 to 0.99, P = 0.008) than women (aOR = 0.93, 95% CI 0.88 to 0.98, P = 0.009), although the sex difference was not statistically significant in this model (sex‐LTL P = 0.37). LTL was not associated with bone mineral density, trabecular bone score, or muscle fat infiltration in the overall or subgroup analyses (P > 0.05). Conclusions LTL was consistently associated with thigh fat‐free muscle volume in men and women. Future research should investigate moderating effects of lifestyle factors (e.g., physical activity, nutrition, or chronic diseases) in the association between LTL and muscle volume.